Treatment and Outcomes among Patients with Cryptococcus gattii Infections in the United States Pacific Northwest - Smith, Rachel M.; Mba-Jonas, Adamma; Tourdjman, Mathieu; Schimek, Trisha; DeBess, Emilio; Marsden-Haug, Nicola; Harris, Julie R. (PLOS ONE, 2014)
Background Cryptococcus gattii is a fungal pathogen causing an emerging outbreak in the United States Pacific Northwest (PNW). Treatment guidelines for cryptococcosis are primarily based on data from C. neoformans infections; applicability to PNW C. gattii infection is unknown. We evaluated the relationship between initial antifungal treatment and outcomes for PNW C.gattii patients. Methods Cases were defined as culture-confirmed invasive C. gattii infections among residents of Oregon and Washington States during 2004–2011. Clinical data were abstracted from medical records through one year of follow-up. Recommended initial treatment for central nervous system (CNS), bloodstream, and severe pulmonary infections is amphotericin B and 5-flucytosine; for non-severe pulmonary infections, recommended initial treatment is fluconazole. Alternative initial treatment was defined as any other initial antifungal treatment. Results Seventy patients survived to diagnosis; 50 (71%) received the recommended initial treatment and 20 (29%) received an alternative. Fewer patients with pulmonary infections [21 (64%)] than CNS infections [25 (83%)] received the recommended initial treatment (p = 0.07). Among patients with pulmonary infections, those with severe infections received the recommended initial treatment less often than those with non-severe infections (11% vs. 83%, p<0.0001). Eight patients with severe pulmonary infections received alternative initial treatments; three died. Four patients with non-severe pulmonary infections received alternative initial treatments; two died. There was a trend towards increased three-month mortality among patients receiving alternative vs. recommended initial treatment (30% vs. 14%, p = 0.12), driven primarily by increased mortality among patients with pulmonary disease receiving alternative vs. recommended initial treatment (42% vs. 10%, p = 0.07). Conclusions C.gattii patients with pulmonary infections – especially severe infections – may be less likely to receive recommended treatment than those with CNS infections; alternative treatment may be associated with increased mortality. Reasons for receipt of alternative treatment among C.gattii patients in this area should be investigated, and clinician awareness of recommended treatment reinforced.